Modeling and control of a novel facade cleaning robot with four-ducted fan drive - Xiao-Peng Li; Xin Wang; Bin Feng (International Journal of Advanced Robotic Systems, 2021)
With the development of modern cities, the demand for cleaning glass curtain walls in urban skyscrapers is increasing, and therefore, many researches on facade cleaning robots have been carried out in the past few decades. In this article, a novel type of facade cleaning robot based on four-ducted fan is proposed. To improve the load capacity of the robot, the lifting and horizontal movement are, respectively, supported by an independent lifting mechanism and a lateral movement mechanism. Unlike the previous passive and active suction, the powerful suction power of the robot is provided by the four-ducted fan. Meanwhile, the obstacle-climbing force is caused by the forward of the four-ducted fan that improves the crossing obstacle ability. In addition, an incremental sliding mode algorithm is applied for controlling the posture when the robot crosses obstacles, which can ensure the stable performance of the cleaning robot under disturbance. Some simulations and experiments are conducted and the results demonstrate the effectiveness and robustness of the designed facade cleaning robot.